Simultaneous Biocementation and Compaction of a Soil to Avoid the Breakage of Cementitious Structures during the Execution of Earthwork Constructions - Laura Morales Hernández; Eduardo Garzón Garzón; Pedro J. Sánchez-Soto; Enrique Romero Morales (Geotechnics, 2023)
This research focuses on the potential for microbial treatment to stabilize compacted soils, which are often utilized in earthwork projects. A silt–clay sand was used to describe a particular kind of soil. The suggested remedy makes use of the soil’s naturally occurring urea and Ca2+, as well as microorganisms introduced to the compaction water. Two alternative initial water-content types were examined: those on the dry side and those close to the ideal Proctor conditions. Bacillaceae microorganisms were used to induce microbial CaCO3 precipitation and improve the hydraulic and mechanical properties of the compacted soil. The samples were biotreated and immediately compacted, so that the precipitation of calcium carbonate during the curing process took place in the contact areas between the particles (biocementation) and in the pore space (bioclogging). A set of techniques were used to study the ageing effects, such as the water-retention curve by dew-points psychrometer, mercury porosimetry intrusion, permeability, ultrasonic pulse velocity, resonant column, and unconfined and tensile-compression tests. During the ageing, it was observed that the bacterial activity consumed water for the hydrolysis of urea and other intermediate reactions to precipitate CaCO3. This process resulted in a retraction of the microstructure and a change in the macrostructure. The bioclogging phenomenon was more evident in the soil microstructure, while the biocementation process was easier to observe in the macrostructure. The suction’s effects on the soil stiffness were studied in detail, and a significant increase was detected. Despite these water-content losses, which caused soil stiffening by increasing the suction, it was still feasible to identify the gradual rise in small-strain stiffness throughout incubation. The unconfined and tensile-compression tests showed a similar progressive increase in terms of peak compressive and peak splitting strength during the incubation. These results are of interest when microbiological treatments are applied in soils to produce cementitious materials, with the present investigation demonstrating a complete study of their geotechnical behaviour.